Uncovering the molecular and immunological defects in multicentric carpotarsal osteolysis syndrome: identification of relevant biomarkers - Najjar, Dorra; Chikhaoui, Asma; Boussetta, Rim; Azouz, Saifeddine; Zarrouk, Sinda; Bouchoucha, Sami; Yacoub-Youssef, Houda (Frontiers in Immunology, 2025)
Multicentric carpotarsal osteolysis (MCTO) is a rare genetic disease characterized by progressive osteolysis, often followed by nephropathy in advanced stages. It’s caused by variants in the MAFB gene. This disease mimics juvenile idiopathic arthritis (JIA) and is often misdiagnosed due to the clinical similarity and rarity of MCTO disease. However, the pathophysiology of MCTO remains largely unknown. While the use of non-steroidal treatment is recommended for patients with JIA, it triggers the onset of nephropathy in patients with MCTO. In this study, we aimed to investigate the clinical, genetic etiology, and immune profiles of patients with MCTO in three Tunisian siblings with MCTO disease. Genetic investigation was performed using Sanger sequencing, and the effect of the variant on the phosphorylation process was explored using the in-silico prediction tool “NetPhos”. We further investigated the expression of 17 immune-related genes using qPCR, and performed immune cell phenotyping using flow cytometry in these patients and in five healthy donors. Twelve inflammatory cytokines were measured using ELISArray. We observed clinical variability among the siblings, and a kidney biopsy revealed focal segmental glomerulosclerosis in one patient. The genetic analysis identified a novel variant in MAFB (c.187C>T; p.(Pro63Ser)) in the three patients, for whom in silico investigation revealed that this variant could lead to alterations in the phosphorylation process. Further investigations revealed that MCTO patients tend to have increased frequencies of non-classical and intermediate monocytes, which may be associated with bone osteolysis. Interestingly, high levels of CD8+ T cells, NK CD56bright cells, and IL8 were detected in a single patient who presented an early-stage nephropathy, which may be a consequence of the use of non-steroidal treatment. Inflammatory and oxidative stress-related genes were overexpressed. In conclusion, we present the first study on Tunisian patients in which the genetic investigation oriented the diagnosis from JIA to MCTO through the identification of a novel variant that affects the phosphorylation of the MafB protein. We suggest that both genetic and immune alterations may contribute to the development of MCTO syndrome and provide preliminary insights into its pathophysiology.